ANALISIS KECEMASAN SEORANG ANAK YANG DITINGGAL MATI SALAH SATU ORANG TUA - Sulfikar K; desi alawiyah; Burhanuddin Buhanuddin (Institut Agama Islam Muhammadiyah Sinjai, 2023)
Death is a fate that no one can avoid. The death of a person does not only involve the person who died but also affects the person left behind. The death of a parent will cause life changes that can cause stress and sadness, this sadness will cause a child to experience grief because of the loss of a loved one due to death. The purpose of this study was to find out how the anxiety felt by a child whose parents died was related to his emotional state which was filled with feelings of loss, sadness, loneliness and lack of love. This study uses a qualitative method with a case study qualitative research type. Methods of data collection carried out using the interview method. The results of this study are to reveal things that are more in-depth and detailed that cannot be uncovered by other methods, the response or reaction felt by a child whose parents have died is anxiety. The conclusion from the results of this study, the authors found anxiety experienced by a child in the form of anxiety about the future, social, economic and cognitive disturbances. The author also finds that a child overcomes his anxiety by using Emotional-Focused Coping techniques